MERAJUT RELASI MENGGENGGAM TRADISI: MASYARAKAT NUSA UTARA DALAM DIPLOMASI MARITIM INDONESIA – FILIPINA (1955−1974) - Syafaat Rahman Musyaqqat (Universitas Negeri Malang, 2019)
Maritime diplomacy between Indonesia and the Philippines began to develop when the two countries had just gained independence and were confronted with the problem of cross-border activities in the people of North Nusa Tenggara. On the one hand, the mobility of the people of North Nusa to Balut Island and Sarangani (Philippines) is commonplace and even has become their tradition. On the other hand, population mobility is an act that can at times lead to politically tense relations for both countries. This article aims to explore maritime diplomacy between Indonesia and the Philippines from 1955 to 1974. Using historical methods, the study's findings show that there is a tendency in the Indonesia-Philippines relationship to understand the maritime traditions of the Sangihe-Talaud community as border communities. This tendency is evident in several policies agreed by the two countries. One of them is the Border Cross Agreement in 1956.Diplomasi maritim antara Indonesia dan Filipina mulai terbangun ketika kedua negara baru saja memperoleh kemerdekaannya dan dihadapkan pada persoalan aktivitas lintas batas (border-cross) masyarakat Nusa Utara. Di satu sisi, mobilitas masyarakat Nusa Utara ke Pulau Balut dan Sarangani (Filipina) merupakan hal yang lumrah bahkan telah menjadi tradisi mereka. Di lain sisi, mobilitas penduduk merupakan tindakan yang sewaktu-waktu dapat menggiring relasi yang menegangkan secara politik bagi kedua negara. Artikel ini bertujuan menelusuri diplomasi maritim antara Indonesia dan Filipina sejak tahun 1955 hingga 1974. Dengan menggunakan metode sejarah, temuan studi menunjukkan bahwa terdapat kecenderungan dalam relasi Indonesia-Filipina untuk saling memahami tradisi bahari masyarakat Sangihe-Talaud sebagai masyarakat perbatasan. Kecenderungan tersebut nampak pada beberapa kebijakan yang disepakati oleh kedua negara. Salah satu diantaranya ialah Border Crosss Agreement pada 1956.